2016
DOI: 10.1111/hepr.12627
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide LL‐37 attenuates infection of hepatitis C virus

Abstract: The VD-associated antimicrobial peptide LL-37 attenuated the infectivity of HCV. This anti-HCV effect of LL-37 may explain the contribution of VD to the improved efficacy of interferon-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The activity of the native LL-37 was significantly greater than scrLL-37, leading us to conclude that LL-37 had a structure-dependent antiviral activity against KSHV. This ability of the native primary structure of LL-37 to inhibit viral infections as opposed to a scrambled version of the peptide has also been observed with a number of other viruses—including DENV (Alagarasu et al, 2017), HAdV19 (Gordon et al, 2005), HCV (Matsumura et al, 2016), HRV (Sousa et al, 2017), HSV-1 (Gordon et al, 2005; Lee et al, 2014), influenza A virus (Barlow et al, 2011; Tripathi et al, 2015a, 2013 White et al, 2017), and RSV (Currie et al, 2013; Harcourt et al, 2016)—suggesting the specific structure, and not simply the charge, of LL-37 is important in its antiviral activity.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The activity of the native LL-37 was significantly greater than scrLL-37, leading us to conclude that LL-37 had a structure-dependent antiviral activity against KSHV. This ability of the native primary structure of LL-37 to inhibit viral infections as opposed to a scrambled version of the peptide has also been observed with a number of other viruses—including DENV (Alagarasu et al, 2017), HAdV19 (Gordon et al, 2005), HCV (Matsumura et al, 2016), HRV (Sousa et al, 2017), HSV-1 (Gordon et al, 2005; Lee et al, 2014), influenza A virus (Barlow et al, 2011; Tripathi et al, 2015a, 2013 White et al, 2017), and RSV (Currie et al, 2013; Harcourt et al, 2016)—suggesting the specific structure, and not simply the charge, of LL-37 is important in its antiviral activity.…”
Section: Discussionmentioning
confidence: 61%
“…The ability of LL-37 to directly inhibit a number of viruses has been reviewed previously (Barlow et al, 2014b), with further activities found against Aichi virus A (Vilas Boas et al, 2017), human adenoviruses 8 and 19 (HAdV-8 and HAdV-19) (Gordon et al, 2005; Uchio et al, 2013), hepatitis C virus (HCV) (Matsumura et al, 2016), human papillomavirus 16 (HPV16) (Buck et al, 2006), human rhinovirus (HRV) (Findlay et al, 2017; Schögler et al, 2016; Sousa et al, 2017), and varicella zoster virus (VZV) (Crack et al, 2012). While LL-37 has only been measured at 0.5 μg/ml in saliva (Bachrach et al, 2006; Takeuchi et al, 2012) and 10 μg/ml in gingival crevicular fluid 29 , the actual physiological concentration may be much higher at sites closer to the oral epithelial cells themselves due to the diffusion of the peptides once released from cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, pretreatment of Huh‐7 cells with different concentrations of LL37 (2‐20 μg/mL) attenuated HCV infection approximately 2 to 10‐fold as shown by decreased intra‐ and extracellular levels of HCV core antigen. Supplementation with vitamin D is thought to induce elevated levels of LL37, which might improve the efficacy of treatment when used in combination with IFN‐based therapy . However, further studies are required to confirm if LL37 exerts its anti‐viral effect independently or in combination with other intrinsic defense factors.…”
Section: Introductionmentioning
confidence: 99%
“…CAMP has also been reported to have antiviral activity against human immunodeficiency virus, influenza A virus, respiratory syncytial virus, and vaccinia virus (62) as well as several other functions in the immune system, such as chemotactic and angiogenic roles (63). Very recently, it was reported that preincubation of cells or HCV with LL-37 attenuates the infectivity of HCV (64), in contrast to our observation here that the exogenous expression of CAMP and LL-37 promotes infectious particle production in BE-KO cells. Although direct comparison is difficult, the discrepancy of the effects of LL-37 on HCV propagation might be attributable to the concentration of LL-37 used in the experiments.…”
Section: Discussionmentioning
confidence: 99%